2022
DOI: 10.3390/ijerph192416534
|View full text |Cite
|
Sign up to set email alerts
|

Food Literacy and Dietary Intake in German Office Workers: A Longitudinal Intervention Study

Abstract: Widespread patterns of poor dietary behavior are a key factor causing the increasing prevalence of chronic diseases around the world. Research has provided initial insights into the potential of food literacy (FL) to empower individuals to improve their dietary behavior. However, studies on FL interventions in working adults are scarce. The intervention delivered in this study was a comprehensive 3-week full time education-based workplace health promotion program (WHPP) that provided the participants with in-d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…These findings suggest that well-designed WHPPs can lead to long-term enhancements in FL and DI, highlighting the importance of FL in expanding food-related knowledge and skills to promote healthier dietary behaviors. This study provides valuable long-term insights into the role of FL in WHPPs, and supports the incorporation of FL in the development of comprehensive workplace health programs to improve dietary intake [33].…”
Section: Do Research Projects Promote Food/nutrition Literacy?supporting
confidence: 56%
“…These findings suggest that well-designed WHPPs can lead to long-term enhancements in FL and DI, highlighting the importance of FL in expanding food-related knowledge and skills to promote healthier dietary behaviors. This study provides valuable long-term insights into the role of FL in WHPPs, and supports the incorporation of FL in the development of comprehensive workplace health programs to improve dietary intake [33].…”
Section: Do Research Projects Promote Food/nutrition Literacy?supporting
confidence: 56%
“…In this study, healthy and balanced nutrition was also found to be significantly associated with all sub-dimensions of FNLI (Tables 3 and 4). Food literacy can empower individuals to improve their eating behavior, promoting healthy eating [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an intervention study in Australian adults confirmed these findings and displayed a positive effect of FL on DB [ 36 ]. With respect to the workplace setting, a longitudinal study in German office workers displayed a positive small-to-moderate influence of FL on working adults’ DB over the course of 18 months following a three-week workplace health promotion program (WHPP) focusing on FL and DB [ 37 ].…”
Section: Introductionmentioning
confidence: 99%